Penggambaran Tokoh Lansia Pada Film Eyang Ti (2021) - Widya Berlian Permatasari (Jurnal Ilmu Komunikasi, 2022)
The elderly often get several stereotypes from society. Not only positive stereotypes, but there are still many who think negatively. Of course this is motivated by the notion that the elderly are weak and helpless, it is only fitting that they should be cared for and treated like small children. Likewise with the depiction of the elderly in the film industry. It can be seen that there are still very few elderly figures circulating in films, including the Indonesian film industry. Many Indonesian films use elderly characters as companion characters, both as mothers, fathers, and even the most extreme as assistants or drivers and of course this depiction is part of age discrimination, especially against the elderly. You can count on the fingers of several Indonesian films that make elderly characters the main character in the story. In 2021, the Indonesian film industry is also presenting films where the main character is an elderly figure. This film was directed by Herwin Novianto by making Widyawati, a 72-year-old senior actor to be the main character in the film. This film is entitled Eyang Ti which depicts the representation of elderly figures in a family. This film also shows the conflicts experienced by Eyang Murti, as the main character, with his family. Act as a grandmother, mother, and in-laws. The description of the analysis researchers use John Fiske's semiotic analysis which is divided into three levels, namely reality, representation, and ideology. So the researchers analyzed the depiction of an elderly character as the main character of the story, namely Eyang Murti.